Processo de erosão de um argissolo utilizando o modelo Wepp - Ibiapina, Thiago Vinicius Barros [UNESP] (2015)
Soil erosion has been the subject of great concern worldwide due to major changes in the planet. These include climate change, and biodiversity loss on the planet, but little commented other changes, but no less important are the changes in nitrogen and phosphorus cycles. Part of this study shows that the carrying of sediments generated by erosion can be the villain of eutrofizações bodies of water. This work was carried out in an area located in the municipality of Tabapuã, northwest of São Paulo, whose geographical coordinates are: Latitude 21 05 '57 S and Longitude 49 01' 02 W. The main objective of this study was to estimate the erosion with the WEPP model in acreage of Tabapuã (SP), and with the following specific objectives: 1) to adjust the model for use in tropical climates like Brazil's climate; 2) apply the model to measure scenarios of possible impacts caused by water erosion for cane sugar crops, corn and soybeans in the study area. There has resulted in the particle size composition of the sediment divided into five fractions corresponding fractions clay, silt, very fine sand, fine sand and sand respectively. Under the conditions of the study the culture of cane sugar was shown to be less protectionist when compared to corn and soybeans. With the generation of climate component to the city of the experiment have been more reliable data to measure the impacts of management in the loss of the study area soils. The WEPP model was efficient in the generation of net erosion values for the studied area in the basin where there is a deposition of sediments